The use of close-range photogrammetry in zooarchaeology: Creating accurate 3D models of wolf crania to study dog domestication - Evin, Allowen; Souter, Thibaud; Hulme-Beaman, Ardern; Ameen, Carly; Allen, Richard; Viacava, Pietro; Larson, Greger; Cucchi, Thomas; Dobney, Keith (Journal of Archaeological Science: Reports, 2016)
Close-range photographic techniques - including photogrammetry - are becoming common tools for constructing three-dimensional (3D) models of artifacts, particularly in archaeological research. Whether models obtained through photogrammetry can be used for zooarchaeological studies requires a systematic examination. In the context of research into dog domestication, we explore whether 3D models of wolf crania, obtained through a photogrammetric approach, accurately describe the original cranium in term of colouration, texture and most importantly, geometry.To answer this question, we compared the topology of 3D models obtained with a high-resolution surface scanner (used as reference geometry) with models reconstructed from the same five wolf crania using photogrammetry. The pairs of models were then compared using both a visual, qualitative and two quantitative approaches. The latter, a geometric comparison computed the deviation map between the pairs of 3D models, which was then followed by a 3D landmark based geometric morphometric approach using corresponding analyses.Our results demonstrate that photogrammetry can produce 3D models with visually satisfying levels of morphological detail in terms of texture, colouration and geometry. In addition, the quantitative comparison of the models revealed an average distance between the two surfaces of 0.088 mm with an average standard deviation of 0.53 mm. The geometric morphometric analyses revealed the same degree of measurement error for the two series of scans (2.04% and 1.95%), with only 6.31% of the morphometric variation being due to the acquisition technique. Photogrammetry, therefore, offers a low cost, easily portable and simple to perform alternative to traditional surface scanning, affording advantages that make it a highly useful tool for zooarchaeological research.